2005
DOI: 10.1080/09541440540000031
|View full text |Cite
|
Sign up to set email alerts
|

Retrieval contexts and the concreteness effect: Dissociations in memory for concrete and abstract words

Abstract: Decades of research on the concreteness effect, namely better memory for concrete as compared with abstract words, suggest it is a fairly robust phenomenon. Nevertheless, little attention has been given to limiting retrieval contexts. Two experiments evaluated intentional memory for concrete and abstract word lists in three retrieval contexts: free recall, explicit word-stem completion, and implicit word-stem completion. Concreteness effects were observed in free recall and in explicit word-stem completion, bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 23 publications
(85 reference statements)
0
14
0
Order By: Relevance
“…Likewise it has been found that concrete words are processed more quickly than abstract words in lexical decision (e.g., Binder, Westbury, McKiernan, Possing, & Medler, 2005;de Groot, 1989;Kroll & Merves, 1986;Roxbury, McMahon, & Copland, 2014;Schwanenflugel et al, 1988;Schwanenflugel & Stowe, 1989) and in word naming (e.g., de Groot, 1989;Schwanenflugel & Stowe, 1989). Concrete words are also remembered better than abstract words (Paivio, 1971;Paivio et al, 1966;ter Doest & Semin, 2005). This processing advantage is considered to be a classical effect in the psycholinguistic literature and it is indeed covered in every textbook on cognitive psychology.…”
Section: The Availability Of Norms Constrains Models Of Lexical Procementioning
confidence: 91%
See 1 more Smart Citation
“…Likewise it has been found that concrete words are processed more quickly than abstract words in lexical decision (e.g., Binder, Westbury, McKiernan, Possing, & Medler, 2005;de Groot, 1989;Kroll & Merves, 1986;Roxbury, McMahon, & Copland, 2014;Schwanenflugel et al, 1988;Schwanenflugel & Stowe, 1989) and in word naming (e.g., de Groot, 1989;Schwanenflugel & Stowe, 1989). Concrete words are also remembered better than abstract words (Paivio, 1971;Paivio et al, 1966;ter Doest & Semin, 2005). This processing advantage is considered to be a classical effect in the psycholinguistic literature and it is indeed covered in every textbook on cognitive psychology.…”
Section: The Availability Of Norms Constrains Models Of Lexical Procementioning
confidence: 91%
“…Of course, to provide convincing evidence for this effect and support an evolutionary account of it, researchers have to test for other (and somewhat more trivial) explanations, such as the possibility that animates are easier to imagine or are more concrete than inanimates. In effect, given that concrete words are remembered better than abstract words (Paivio, 1971;Paivio, Yuille, & Smythe, 1966;ter Doest & Semin, 2005), and because concreteness is one of the most important variables accounting for the recall rates of words presented in unrelated lists (Nairne et al, 2013), this variable must be controlled for when investigating animacy effects. As a result, the availability of concreteness norms for words is essential for researchers who seek to investigate memory.…”
Section: Availability Of Norms Helps the Control Of Variablesmentioning
confidence: 99%
“…On each trial in the study phase, a word was presented in the center of a 17″ monitor controlled by a Macintosh G3 computer using PsyScope (Cohen et al, 1993 ). Each word was presented for 2 s, followed by 3 s of blank screen before presentation of the next word (ter Doest and Semin, 2005 ). A total of 60 words were presented for study, in a different random order to each participant.…”
Section: Methodsmentioning
confidence: 99%
“…Coding procedures for recall responses were adopted from those used in previous studies (e.g., ter Doest and Semin, 2005 ). Responses were judged correct if they were identical to, or were inflectional or misspelled variants of words on the study list (e.g., we accepted shelf for shelves , and plyers for pliers ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation